Lipids of adult brown shrimp, Crangon crangon: seasonal variations in fatty acids class composition - Mika, Adriana; Gołębiowski, Marek; Skorkowski, Edward; Stepnowski, Piotr (Journal of the Marine Biological Association of the United Kingdom, 2014)
Sea food is very rich in lipids. The brown shrimp, Crangon crangon is a most popular and very valuable taxon in the White Sea, in the Mediterranean and in the Black Seas. The aim of this study was to determine the seasonal variations of lipids in C. crangon muscle tissue using gas chromatography–mass spectrometry. The lipids were separated into groups: neutral lipids (triacylglycerols, free fatty acids, sterols) and polar lipids (phospholipids), by high performance liquid chromatography with a laser light-scattering detector. Fatty acids were identified using the GC-MS technique. The mainly fatty acids were 16:0, 18:0 (saturated FAs), 16:1, 18:1 (monounsaturated FAs), 20:4 (ARA), 20:5 (EPA) and 22:6 (DHA). The largest amounts of fatty acids in the muscle were observed in spring; these were the result of collecting food after winter and before reproduction. The muscle lipid content was 32.2 ± 1.8 mg g −1 . The summer was the poorest season and the lipid value was 7.7 ±0.4 mg g −1 . The levels of muscle neutral lipids (NL) oscillated between 80% (autumn) and 90% (spring). The temperature and salinity has a significant influence on content and profile of fatty acids. This work will help to understand the biology, the seasonal variation in lipid mass, lipid classes content and fatty acids profile in the abdominal muscle of C. crangon .